Fake News Reporting by Journalists: National and Islamic Law Perspective - Jamilah, Ummi; Iwan, Iwan (PDIH Untag Semarang, 2024)
This study aims to analyze and explain the factors contributing to the occurrence of fake news reporting by journalists, as well as examine the issue of fake news from the perspective of national law and Islamic law. The research adopts a normative juridical approach, combining empirical and case study methods. The findings reveal that the primary factors behind fake news reporting by journalists include the pressure to deliver news rapidly, insufficient oversight, and the lack of strict regulations in enforcement. From the perspective of national law, provisions regarding the dissemination of fake news are explicitly regulated in the Information and Electronic Transactions Law (UU ITE) and the Criminal Code (KUHP). Despite the existence of laws such as UU ITE and KUHP to address fake news, enforcement is often hindered by concerns over press freedom, difficulties in proof, and varying interpretations of the law. The dissemination of fake news by journalists leads to a decline in public trust and social polarization. While most fake news cases are resolved through legal channels, preventive efforts such as media literacy, strengthening journalistic ethics, and collaboration with social media platforms are crucial in the current era. From the perspective of Islamic law, the spread of fake news is strictly prohibited, and Muslims are obligated to perform *tabayyun* (verification) before sharing information to avoid slander and sin.